2020
DOI: 10.3390/admsci10030048
|View full text |Cite
|
Sign up to set email alerts
|

The Relations between Dynamic Capabilities and Core Competencies on the Case of Polish Companies

Abstract: This article deals with the relationship between dynamic capabilities and core competencies of companies. Both categories extend the resource-based view of the firm. They are difficult to work out, but thanks to their durability and universality they enable to achieve a sustainable competitive advantage. Due to intensive changes in the business environment and increasing difficulty in forecasting them, the importance of adaptability based on both categories increases. The presented results of the research of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…, 1997) to the development of a firm's core competence. Communestrating this, in the study of Polish companies Ceglinski (2020) found that a firm's dynamic capability discovers new opportunities, moulds its existing capabilities and continuously modifies them, which he asserted is pivotal to entering new markets (Linde et al. , 2021; Helfat et al.…”
Section: A Theoretical Framework For the Long-term Growth Of A Firm V...mentioning
confidence: 99%
“…, 1997) to the development of a firm's core competence. Communestrating this, in the study of Polish companies Ceglinski (2020) found that a firm's dynamic capability discovers new opportunities, moulds its existing capabilities and continuously modifies them, which he asserted is pivotal to entering new markets (Linde et al. , 2021; Helfat et al.…”
Section: A Theoretical Framework For the Long-term Growth Of A Firm V...mentioning
confidence: 99%
“…Dynamic capability is the capability to create excellent working conditions for all employees to enhance the capability to take a perilous project by generating radical innovation (Ceglinski, 2020). The process involves blending values, ideas and assumptions to determine the interaction with the structure and the decision-making process by generating behavioural norms (Affuah, 2003; Hofstede et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In times of existing complexity and changes in the business environment, the possibility of forecasting is increasingly limited. Adaptability is crucial, not only for obtaining a sustainable competitive advantage in the sector but also for the survival and competitiveness of the business [11]. In addition to competitive advantage, the issue regards management activities conducted to maintain the unique attributes of the business [12].…”
Section: Introductionmentioning
confidence: 99%